Investigating Grape Insurance in the Conegliano-Valdobbiadene Prosecco Docg Area, Economic Analysis and Assessment of Policy Measures, Period 2014-2017 - Antonio De Pin; Pier Paolo Miglietta; Benedetta Coluccia; Fabian Capitanio (Current Aspects in Business, Economics and Finance Vol. 2, 2022)
Agricultural insurance is essential for the protection of crop products. By decreasing insurance firms’ desire to assume climatic risks, the growing frequency of extreme weather occurrences in Italy has a significant impact on the dynamics of the crop insurance market. In this context, this study focuses on the demand for insurance in the Controlled and Guaranteed Designation of Origin (Docg) area of Conegliano-Valdobbiadene. The objective of the analysis is to provide a very detailed snapshot of adherence to agricultural policy measures, to fill the knowledge gap in the attitude of winegrowers towards insurance. The study starts from the microdata of the individual insured farm at the municipal level, preliminarily providing an economic representation of the viticulture of the Docg Prosecco district. Second goal is to define a suitable assessment of the insurance demand, by innovative indicators, identifying the main economic effects of public contributions for the three subjects involved in the market: winegrowers, public stakeholders, and insurance companies. The research provides interesting analysis and discussion of the results, and possible policy implications. In particular, the effect of public measure is investigated using the subsidy efficiency index (SEI). Its overall positivity underlines the relative efficiency of the level of the grants. The capability to represent the real set-up of subsidized grape insurance in such a defined context can feature a significant merit to address knowledge transfer to policy makers and stakeholders.